A Decision‐Aid Improves Clinician Practice and Associated Patient Compression Stocking Adherence - Laila Bar; Susan Brandis; Rachel Wenke; Darryn Marks (International Wound Journal, 2026)
ABSTRACT Adherence to compression stocking wear is essential for reducing venous leg ulcer recurrence, yet adherence rates remain low. This study examined the relationship between a novel digital clinical decision‐aid (the Personalized and Multidimensional Compression Assessment and Intervention [PAMCAI]), clinician practice, and patient adherence with compression stocking use, by embedding a prospective comparative cohort study within a pilot randomized controlled trial. The clinical notes of occupational therapists using PAMCAI were compared with those not using PAMCAI on their documentation of adherence and frequency of wear, identification of patient‐specific barriers and attempts to address barriers. The relationship between higher documentation scores and patient adherence was also explored. Thirty‐six medical records from 18 patients demonstrated significantly higher documentation scores when PAMCAI was used for all three categories ( p < 0.001). Improvements in adherence were positively associated with documentation quality in the targeted categories ( p < 0.001). These findings indicate that PAMCAI supports practice changes that translate to improved patient adherence, highlighting the potential value of clinician‐focused decision‐aids in venous leg ulcer care.